2013
DOI: 10.1021/ef401338c
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Heavy Oil Recovery in Sandstone Cores Using TiO2 Nanofluids

Abstract: Anatase and amorphous TiO2 nanoparticles were used to improve recovery of heavy oil from sandstone cores. Before performing core floods, the stability of nanoparticles at different salinities was tested using ζ potential and ultraviolet–visible (UV–vis) methods. While water recovered only 49% of the oil in the core flood experiments, 0.01% anatase structure solution recovered 80% of the oil after injecting two pore volumes at optimum conditions. To understand the mechanism responsible for improved recovery, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
153
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(157 citation statements)
references
References 30 publications
4
153
0
Order By: Relevance
“…The use of nanoparticles (NPs) for enhanced oil recovery (EOR) has received intensive attention since 2008, and much work has been conducted that can be generally categorized as: (i) the development of 'contrast-agent' type NPs to improve the detection limitation of seismic and EM techniques for better reservoir characterization [1][2][3]; (ii) the use of NPs as property modifiers, i.e., to alter rock wettability and interfacial tension at the oil/water interface in order to increase oil recovery rates [4][5][6][7]; and (iii) the use of NPs for conformance control such as nanoparticle-stabilized emulsions, and gelation materials to block the easy flow paths [8,9]. All these applications require nanoparticles to transport long distances in reservoir rocks with minimal retention.…”
Section: Introductionmentioning
confidence: 99%
“…The use of nanoparticles (NPs) for enhanced oil recovery (EOR) has received intensive attention since 2008, and much work has been conducted that can be generally categorized as: (i) the development of 'contrast-agent' type NPs to improve the detection limitation of seismic and EM techniques for better reservoir characterization [1][2][3]; (ii) the use of NPs as property modifiers, i.e., to alter rock wettability and interfacial tension at the oil/water interface in order to increase oil recovery rates [4][5][6][7]; and (iii) the use of NPs for conformance control such as nanoparticle-stabilized emulsions, and gelation materials to block the easy flow paths [8,9]. All these applications require nanoparticles to transport long distances in reservoir rocks with minimal retention.…”
Section: Introductionmentioning
confidence: 99%
“…The surfactant in turn affected the interactions between the nanoparticles by increasing repulsion forces between the SiO 2 NPs. The lack of surfactant at higher SiO 2 NPs concentrations indicates that the SiO 2 NPs produced larger SiO 2 nanoaggregates with larger-thansuitable diameters (Cieslinski and Krygier 2014;Ehtesabi et al 2014). The smaller diameters of nanoaggregates reported in previous findings were most likely the consequence of longer sonication times which yielded a more thorough mixture of the NPs into the suspension.…”
Section: Heavy Crude Oilmentioning
confidence: 67%
“…The smaller diameters of nanoaggregates reported in previous findings were most likely the consequence of longer sonication times which yielded a more thorough mixture of the NPs into the suspension. Furthermore, unlike similar studies detailing various nanoaggregates, we used a higher concentration of 5% brine to generate higher aggregation rates and larger nanoaggregate sizes (Ehtesabi et al 2014;Hendraningrat and Torsaeter 2014). This variance in brine characteristics may serve as a Ò 20: e raw data, and f processed data in the Loess Model in R possible explanation for the larger size of nanoaggregates detected in our study in which the large standard deviations observed for the nanoaggregate size indicate a high degree of polydispersity of the nanofluids.…”
Section: Heavy Crude Oilmentioning
confidence: 99%
“…Stabilize wellbore; reduce filter loss; improve rheology; increase thermal stability Alimohammadi et al, [14] Sharma et al, [15] Parizad and Shahbazi, [16] Ehtesabi et al, [17] Qiu, [18] and Di et al [19] 2. Change the wettability of porous surfaces of sandstone 3.…”
Section: Nanofluidmentioning
confidence: 99%